Substitusi Beras dengan Jagung pada Pembuatan Lempeng Gendar dengan Cara yang Disederhanakan - Ag. Pamudji Rahardjo; Haryadi Haryadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1998)
Traditional rice crackers (lempeng gendar) were prepared by a simplified processing method involving milling of rice, mixing of the flour with boiled water and traditional alkaline salt and NaCI, steaming of the dough on trays, cooling, slicing, drying, and finally frying. The raw material was varied by adding corn flour to the rice (IR-36 and IR-42) flours to get the proportions of 100, 75, 50, 25% and 0 % (100% corn flour). Higher amilose content of the flours (IR-42 rice 15.1%, IR-36 18.4%, and corn 26.8%) gave higher moisture content of the raw rice crackers produced by the simplified method, smaller expansion of the fried product with a consequence of smaller higroscopicity, but resulted in poorer crispiness. Rice crackers made from IR-36 rice flour substituted with 0r75% corn flour, and those made from IR-42 rice flour substituted with 0-50% showed significantly no difference in the overall acceptability with the poduct made from IR-36 rice flour by adopting the traditional processing way. Therefore, the simplified method, which took a shorter time, might replace the traditional way, and substitution of rice with corn to produce the traditional rice crackers was adoptable.